Rare benign tumour at an unusual site-angiomyoma of the ear: a case report and literature review - Reddy, Sridhar; Gonuru, Vinod Kumar; Ravipati, Sri Vishnupriya (International Journal of Research in Medical Sciences, 2022)
The objective was to demonstrate the occurrence of the rare benign tumour angiomyoma or angioleiomyoma in the ear canal. Angiomyoma, known as vascular leiomyoma or angioleiomyoma, is a benign tumour of smooth muscle arising from the muscular wall of veins and comprises less than 5% of all benign smooth muscle tumours. Peak incidence is observed in the fourth to sixth decades with the site of predilection being the subcutaneous tissue in the lower limbs, followed by the upper limbs. This is in contrast to our present case, where the angiomyoma was found in the ear canal which is very rare. A 60-year-old female, an otherwise healthy patient presented with fullness in the left ear. Excision of the swelling was done without any complications.